Clinical Correlation between Cervical Cancer Screening Using Pap Smear Test - Zubaida Shaheen, Muhammad Sami Ullah, Sajida Imran, Nabila Akram, Mohammed Alorini, Urwa Sarwar, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The study's objective is to evaluate the effectiveness of the Pap smear screening procedure for identifying precancerous lesions. Study Design: Prospective study Place and Duration: Department of Pathology, Nishtar Medical University Multan, From 1st October, 2021 to 31 March, 2022. Methods: There were 162 females had age 18-50 years were presented in this study. All of the women were given a complete physical examination, including a speculum exam and a vaginal exam, and their medical histories were recorded. Women's cervical cancer screenings often involved a Pap smear. Using an Ayre spatula, a smear was collected and spread over a labelled glass slide before being stored in 95% ethyl alcohol and delivered to the Pathology Department for cytopathological testing. SPSS 24.0 was used to analyze all data. Results: Among 162 females, 45 (27.8%) had age 18-30 years, 73 (45.1%) were aged between 31-40 years and 44 (27.2%) patients had 41-50 years. Mean BMI of the females was 22.4 ±6.52 kg/m2. Frequency of smokers was 4 (2.5%). Most common complaint was vaginal discharge, followed by irregular menstrual cycle and abdominal pain. We found that 63 (32.7%) cases had no pathology, frequency of inflammatory was 49 (30.2%) cases, atypical squamous cells of undetermined significance (ASUS) was 28 (17.3%), low-grade squamous intraepithelial lesions (LSILs) was 8 (4.9%) and high-grade squamous intraepithelial lesions (HSILs) was 5 (3.1%). As per HPV, low risk and high risk virus was found in 11 (6.8%) cases. Conclusion: The Pap smear is an easy, quick, and inexpensive way to check for cervical epithelial precancerous abnormalities. It has the potential to be employed as a routine screening tool, leading to better treatment outcomes and lower death rates. Increased detection of these lesions is facilitated by the Pap test and the HPV-PCR test. Keywords: Cervical Cancer, Pap smear Test, HPV, Pathology